Computerized Accounting Information System in Nepalese SMEs - Sapkota, Shiba Prasad (Journal of Balkumari College, 2022)
The conversion from a manual accounting system to a computerized accounting system blended accounting with information technology in recent decades. In the area of accounting and finance, the use of computer software enables SMEs quick reporting and easy processing and storage of financial information.To address the issue of whether Nepalese SMEs ready to adopt CAIS, this study aimed to examine the factors that influence Nepalese SMEs to adopt CAIS.